Noise detection in classification problems - Garcia, Luís P. F.; Lorena, Ana C.; de Carvalho, André C. P. L. F. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2017: Anais do XXX Concurso de Teses e Dissertações, 2017)
Large volumes of data have been produced in many application domains. Nonetheless, when data quality is low, the performance of Machine Learning techniques is harmed. Real data are frequently affected by the presence of noise, which, when used in the training of Machine Learning techniques for predictive tasks, can result in complex models, with high induction time and low predictive performance. Identification and removal of noise can improve data quality and, as a result, the induced model. This thesis proposes new techniques for noise detection and the development of a recommendation system based on meta-learning to recommend the most suitable filter for new tasks. Experiments using artificial and real datasets show the relevance of this research.